2020
DOI: 10.1038/s41377-019-0231-1
|View full text |Cite
|
Sign up to set email alerts
|

Acousto-optic modulation of photonic bound state in the continuum

Abstract: Photonic bound states in the continuum (BICs) have recently been studied in various systems and have found wide applications in sensors, lasers, and filters. Applying BICs in photonic integrated circuits enables low-loss light guidance and routing in low-refractive-index waveguides on high-refractive-index substrates, which opens a new avenue for integrated photonics with functional single-crystal materials. Here, we demonstrate high-quality integrated lithium niobate microcavities inside which the photonic BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(98 citation statements)
references
References 39 publications
1
97
0
Order By: Relevance
“…Key elements for photonic integrated circuits such as waveguides, microcavities, directional couplers, (de)multiplexers, and modulators have recently been experimentally demonstrated in low-refractive-index waveguides on high-refractive-index substrates. [93,[98][99][100] A schematic of the envisioned photonic integrated circuits relying on BIC low-refractive-index waveguides on high-refractive-index substrates is depicted in Figure 4d. This platform used an easy-to-etch organic polymer on top of a lithium niobate layer where the light is guided.…”
Section: Bics For Light Guidingmentioning
confidence: 99%
“…Key elements for photonic integrated circuits such as waveguides, microcavities, directional couplers, (de)multiplexers, and modulators have recently been experimentally demonstrated in low-refractive-index waveguides on high-refractive-index substrates. [93,[98][99][100] A schematic of the envisioned photonic integrated circuits relying on BIC low-refractive-index waveguides on high-refractive-index substrates is depicted in Figure 4d. This platform used an easy-to-etch organic polymer on top of a lithium niobate layer where the light is guided.…”
Section: Bics For Light Guidingmentioning
confidence: 99%
“…[ 184 ] The underlying mechanism is that through the photons and phonons coupling, it will give rise to a carrier density variation in the media, which further changes the complex refractive index of the transparent material, equivalent to the phase and absorption modulation. [ 29,71,185,186 ]…”
Section: Acousto‐optic Effect and Its Applications For 2d Materialsmentioning
confidence: 99%
“…[184] The underlying mechanism is that through the photons and phonons coupling, it will give rise to a carrier density variation in the media, which further changes the complex refractive index of the transparent material, equivalent to the phase and absorption modulation. [29,71,185,186] Nowadays, the development of AO devices has hit a bottleneck where high-quality acousto-optic materials (e.g., the figure of merit and acoustic attenuation) are in great demand. [186,187] Although traditional AO materials have been widely investigated include TiO 2 , TeO 2 , and As 2 S 3 [188] suitable for visible to near-infrared wavelength; GaAs, ZnTe, GaP, ZnS, and CdS suitable for far-infrared wavelength, and among others, there still limitations in the applications such as the AO devices operating in the gigahertz range.…”
Section: Materials With Acousto-optic Effectmentioning
confidence: 99%
“…Because the BIC mechanism promises tight confinement of photons in a high-refractive-index material surrounded by a low-refractive-index environment, the reported optical BICs are mostly realized in the conventional structures, such as passive photonic crystal slabs [47], waveguide arrays [48], nanoparticles [49], and anisotropic dielectric layers [50]. However, it has also been reported that the optical BICs can exist in a high-refractive-index substrate with low-refractive-index waveguides atop by precisely tuning the dimensional parameters to achieve destructive interference between the leaky channels to the substrate [51][52][53], which can be explained by Friedrich-Wintgen BICs [54].…”
Section: Introductionmentioning
confidence: 99%